Acoustic surface phonons of graphene on Ni(111). (April 2016) - al Taleb, Amjad; Anemone, Gloria; Farías, Daniel; Miranda, Rodolfo
Abstract: The structure and the low-energy phonon dispersion of graphene (Gr) on Ni(111) have been experimentally investigated with helium atom scattering (HAS). The Rayleigh mode observed for Gr/Ni(111) is almost identical to the one measured on clean Ni(111). The energy of the flexural ZA mode at the Γ ¯ point was found to be ∼20 meV, significantly lower than the value predicted by recent DFT calculations. The HAS diffraction spectra reveal that the graphene layer has a three-fold symmetry, with a lattice constant a = (2.48 ± 0.02) Å and shows an effective step-defect scattering reduction when the Ni(111) is covered with a graphene sheet. Gr/Ni(111) surface is a very efficient and inert mirror for He atoms, with a specular reflectivity of ca. 20%. The predominant role of inelastic scattering in Gr/Ni(111) is revealed by analysis of the diffraction spectra background and Debye–Waller measurements.